Goal motives and multiple-goal striving in sport and academia: A person-centered investigation of goal motives and inter-goal relations - Healy, L.; Ntoumanis, Nikos; Duda, J. (Elsevier, 2016)
Objectives: This investigation extended the goal striving literature by examining motives for two goals being pursued simultaneously. Grounded in self-determination theory, we examined how student-athletes' motives for their sporting and academic goals were associated with inter-goal facilitation and interference. Design: Cross-sectional survey. Methods: UK university student-athletes (n = 204) identified their most important sporting and academic goals. They then rated their extrinsic, introjected, identified and intrinsic motives for these goals and completed questionnaires assessing inter-goal facilitation and interference. Results: Using a person-centered approach via latent profile analysis, we identified three distinct profiles of goal motives. Auxiliary analyses showed that the profile with high identified motives for both goals reported greater inter-goal facilitation. Conclusions: Extending the previous literature, the findings demonstrate the benefits of autonomous motives when simultaneously pursing goals in sport and academia.